2021
DOI: 10.14218/jcth.2021.00050
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin Attenuates Lipid Accumulation by Increasing Energy Expenditure and Autophagy Regulated by Phosphorylating AMPK

Abstract: Background and Aims: Lipid accumulation is the major characteristic of non-alcoholic fatty liver disease, the prevalence of which continues to rise. We aimed to investigate the effects and mechanisms of icaritin on lipid accumulation. Methods: Cells were treated with icaritin at 0.7, 2.2, 6.7, or 20 µM for 24 h. The effects on lipid accumulation in L02 and Huh-7 cells were detected by Bodipy and oil red O staining, respectively. Mitochondria biogenesis of L02 cells was detected by MitoTracker Orange staining. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The role of autophagy in obesity is shown in a recent study by Zhang et al demonstrating that inhibition of autophagy through the downregulation of FOXO3 leads to lipid accumulation in adipocytes of mice ( 61 ). The association between autophagy inhibition and adipocyte lipid accumulation was also described in a study by Wu et al The use of icaritin, an osteoinductive agent, attenuated lipid accumulation with an increase in autophagy flux ( 62 ). As adipocyte lipid accumulation is closely related to obesity, this suggests that autophagy may participate in regulating obesity condition by inhibiting lipid accumulation.…”
Section: Sirt1-mediated Autophagy and Endocrine Disordersmentioning
confidence: 71%
“…The role of autophagy in obesity is shown in a recent study by Zhang et al demonstrating that inhibition of autophagy through the downregulation of FOXO3 leads to lipid accumulation in adipocytes of mice ( 61 ). The association between autophagy inhibition and adipocyte lipid accumulation was also described in a study by Wu et al The use of icaritin, an osteoinductive agent, attenuated lipid accumulation with an increase in autophagy flux ( 62 ). As adipocyte lipid accumulation is closely related to obesity, this suggests that autophagy may participate in regulating obesity condition by inhibiting lipid accumulation.…”
Section: Sirt1-mediated Autophagy and Endocrine Disordersmentioning
confidence: 71%
“…Our previous study also demonstrated that ICT regulates autophagy depending on the cell status of 3 T3-L1 cells and C2C12 cells. 33 ICT has been reported to regulate autophagy via AMPK. 14,33 ICT has also been reported to inhibit skin fibrosis by regulating AMPK and the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…33 ICT has been reported to regulate autophagy via AMPK. 14,33 ICT has also been reported to inhibit skin fibrosis by regulating AMPK and the Wnt/β-catenin pathway. 34 We therefore assumed that ICT alleviates DTX-induced skin injury through activating AMPK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although vitamin E and pioglitazone have been demonstrated to be beneficial for NAFLD patients, the United States Food and Drug Administration hasn’t approved any specific drugs [ 6 ]. However, our previous studies have demonstrated that flavonoids such as naringenin and icaritin have obvious effects on ameliorating NAFLD [ 7 , 8 ]. As a kind of flavonoid, psoralen is the major antioxidant of Medik (syn.…”
Section: Introductionmentioning
confidence: 99%